Real-life short-term effectiveness of anti-osteoporotic treatments: a longitudinal cohort study - Giovanni Adami; Irene Gavioli; Maurizio Rossini; Ombretta Viapiana; Giovanni Orsolini; Camilla Benini; Eugenia Bertoldo; Elena Fracassi; Davide Gatti; Angelo Fassio (Therapeutic Advances in Musculoskeletal Disease, 2022)
Introduction: Randomized clinical trials have shown that anti-osteoporotic treatments can increase bone mineral density (BMD) and reduce the incidence of fragility fractures. However, data on the real-life effectiveness of anti-osteoporotic medications are still scarce. Methods: We conducted a cohort study on women at high risk of fracture. We retrieved clinical and densitometric data from the DeFRA database, which derives from the DeFRA tool, a web-based fracture risk assessment tool. Multivariable Cox regression survival models were employed to analyze the effectiveness of different anti-osteoporotic drugs on fracture. In sensitivity analyses, we conducted 1:1 propensity score matching analyses. Results: Data on 50,862 women were available. Among these, 3574 individuals had at least two consecutive visits. The crude fracture rate was 91.9/1000 person-year for non-treated patients. The crude fracture rate in bisphosphonate users was 72.1/1000 person-year, in denosumab users was 58.2/1000 person-year, and in teriparatide users was 19.3/1000 person-year. Overall, we found that bisphosphonate use was associated with a 30% lower risk of fracture compared to no treatment [adjusted hazard ratio (aHR): 0.70, 95% confidence interval (CI): 0.50–0.98]. Treatment with denosumab and teriparatide were associated with 60% and 90% lower risk of fracture, respectively (aHR: 0.43, 95% CI: 0.24–0.75 and aHR: 0.09, 95% CI: 0.01–0.70). Bisphosphonate use was associated with a lower risk of fracture only after 1 year of treatment. Conclusion: In conclusion, we found that all anti-osteoporotic medications considered in the study effectively reduced the risk of fracture in the real-life. The effect of bisphosphonate on fracture risk was apparent only after the first year of treatment. Our findings do not support the use of bisphosphonates in patients at imminent risk of fracture.